Defect induced modification of structural, topographical and magnetic properties of zinc ferrite thin films by swift heavy ion irradiation - Raghavan, Lisha; Joy, P. A.; Vijaykumar, B. Varma; Ramanujan, R. V.; Anantharaman, M. R. (Nuclear Instruments & Methods In Physics Research Section B-Beam Interactions With Materials And Atoms, 2017)
Swift heavy ion irradiation provides unique ways to modify physical and chemical properties of materials. In ferrites, the magnetic properties can change significantly as a result of swift heavy ion irradiation. Zinc ferrite is an antiferromagnet with a Neel temperature of 10 K and exhibits anomalous magnetic properties in the nano regime. Ion irradiation can cause amorphisation of zinc ferrite thin films; thus the role of crystallinity on magnetic properties can be examined. The influence of surface topography in these thin films can also be studied. Zinc ferrite thin films, of thickness 320 nm, prepared by RF sputtering were irradiated with 100 MeV Ag ions. Structural characterization showed amorphisation and subsequent reduction in particle size. The change in magnetic properties due to irradiation was correlated with structural and topographical effects of ion irradiation. A rough estimation of ion track radius is done from the magnetic studies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Spin glass; Swift heavy ion; Zinc Ferrite

Magnetically tunable liquid dielectric with giant dielectric permittivity based on core-shell superparamagnetic iron oxide - Vinayasree, S.; Nitha, T. S.; Tiwary, C. S.; Ajayan, P. M.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2018)
A liquid dielectric based on a core-shell architecture having a superparamagnetic iron oxide core and a shell of silicon dioxide was synthesized. The frequency dependence of dielectric properties was evaluated for different concentrations of iron oxide. The dependence of magnetic field on the dielectric properties was also studied. Aqueous ferrofluid exhibited a giant dielectric constant of 6.4 x 10(5) at 0.1 MHz at a concentration of 0.2 vol% and the loss tangent was 3. The large rise in dielectric constant at room temperature is modelled and explained using percolation theory and Maxwell-Wagner-Sillars type polarization. The ferrofluid is presumed to consist of nanocapacitor networks which are wired in series along the lateral direction and parallel along longitudinal direction. On the application of an external magnetic field, the chain formation and its alignment results in the variation of dielectric permittivity.

Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex